2009
DOI: 10.1016/j.socscimed.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Public health works: Blood donation in urban China

Abstract: Recent shifts in the global health infrastructure warrant consideration of the value and effectiveness of national public health campaigns. These shifts include the globalization of pharmaceutical research, the rise of NGO-funded health interventions, and the rise of biosecurity models of international health. We argue that although these trends have arisen as worthwhile responses to actual health needs, it is important to remember the key role that public health campaigns can play in the promotion of national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…For example, during China’s national campaign to promote safe donation, which used celebrities and a patriotic message, the number of voluntary blood donors rose from 55 to 96 320 in one city between 1993 and 2001. 91 In Ghana, analysis of a low-cost radio campaign that promoted voluntary blood donation from 2003 to 2006 showed an associated high response from young male donors attending for repeat donation who had not previously done so. 92 …”
Section: Evidence For Health Behaviour Changementioning
confidence: 99%
“…For example, during China’s national campaign to promote safe donation, which used celebrities and a patriotic message, the number of voluntary blood donors rose from 55 to 96 320 in one city between 1993 and 2001. 91 In Ghana, analysis of a low-cost radio campaign that promoted voluntary blood donation from 2003 to 2006 showed an associated high response from young male donors attending for repeat donation who had not previously done so. 92 …”
Section: Evidence For Health Behaviour Changementioning
confidence: 99%
“…To meet this challenge, China must address the cultural and social barriers in donor recruitment and retention. One prominent cultural barrier relates to the deeply rooted traditional belief that blood is a vital bodily element and loss of blood will be a detriment to long‐term health and vitality 29‐31. This belief deters many people from donation because of the fear of lost health and the depletion of vitality, which would occur as the result of the blood donation .…”
Section: Blood Supply In Chinamentioning
confidence: 99%
“…One prominent cultural barrier relates to the deeply rooted traditional belief that blood is a vital bodily element and loss of blood will be a detriment to long-term health and vitality. [29][30][31] This belief deters many people from donation because of the fear of lost health and the depletion of vitality, which would occur as the result of the blood donation. 32 It also hinders the initiative to increase the volume of whole blood collected at each donation.…”
Section: Social and Cultural Barriers In Donor Recruitment And Retentionmentioning
confidence: 99%
“…A number of previous studies of donor motivation around the world have identified several motivating factors for donation such as altruism, perceived social normative pressure, influence by friends or family members, convenience to donate, previous good experience, incentives, self‐efficacy, direct marketing, advertising. [14–20]. Barriers include negative social norms, previous bad experience, fear, short‐term donor deferral, inconvenience, lack of awareness, personal values.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers include negative social norms, previous bad experience, fear, short‐term donor deferral, inconvenience, lack of awareness, personal values. [14,18–21]. It is noted that different donor groups may be driven by different motivations.…”
Section: Discussionmentioning
confidence: 99%